Progress on Iridium-Catalyzed Hydrosilylation of Alkenes and Alkynes - Gao, Weiwei; Ding, Shengtao (Synthesis, 2020)
iridiumcatalysishydrosilylationalkenesalkynesHydrosilylation of multiple carbon–carbon bonds is a well-known process for the construction of organosilicon compounds. Nowadays, precious metal catalysts, especially platinum complexes, still occupy dominant positions in such processes. However, one important member of the precious metal family, iridium, is less used in this field. As early research mainly focused on developing stable and effective iridium catalysts, recent advances have disclosed the specific efficiency of simple iridium catalytic systems in the synthesis of functional organosilicon compounds. This short review summarizes the utilization of iridium complexes for the hydrosilylation of alkenes and alkynes, with an emphasis on the recent advances published in the last decade.1 Introduction2 Iridium-Catalyzed Hydrosilylation of Alkenes3 Iridium-Catalyzed Hydrosilylation of Alkynes4 Conclusions and Perspectives